VIKTIMISASI ANAK KORBAN PENYALAGUNAAN NARKOBA - Henky Fernando; Yuniar Galuh Larasati; Syahrul Akmal Latif (Faculty of Law, Universitas Lampung, 2022)
The involvement of children in drug abuse cases not only positions children as victims but also creates victimization of children. This study not only describes the involvement of children in drug abuse but also explains the victimization of child victims. This study uses a qualitative descriptive. Data collection was collected by reading 2,000 online news texts using the search keyword